Atypical Presentation of Kimura’s Disease in a Male Patient: A Case Report and Review of Literature - Zahra A. Natsha; Islam A. Hamarsheh; Rawan S. Utt; Bassam Abu Alrob; Adnan A. Wahdan (Case Reports in Medicine)
Kimura’s disease (KD) is a rare chronic inflammatory condition of unknown aetiology. It is a benign disease that might mimic a neoplastic process. It primarily affects the head and neck region, presenting as deep subcutaneous masses, and is often accompanied by triad regional lymphadenopathy, salivary gland involvement, and high serum immunoglobulin E (IgE) levels. Here, we report the second documented case of KD in Palestine diagnosed in a 28-year-old male patient who presented with lymphadenopathy and increased serum immunoglobulin E and G (IgE and IgG) associated with intermittent abdominal pain, generalised fatigue, hepatomegaly, cardiomyopathy, reactive airway disease, peripheral vasculopathy, peripheral neuropathy, and focal segmental glomerulosclerosis. The patient was managed with steroids and an immunosuppressant (Azathioprine) with a moderate response for two years. In 2021, treatment with Mycophenolate Mofetil was initiated, which was more effective than Azathioprine.